Trust and Fiscal Performance: A Panel Analysis with Swiss Data - Christoph A. Schaltegger; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2005)
Citizens are willing to abandon their short-term financial interest in free-riding considerably, if governments act in their interest, if procedures of the public decisions-making process are felt to be fair and if other fellow-citizens have to contribute also an adequate share to the community. In such a situation trustworthiness of a government and trust in a government is high. This paper provides empirical evidence that trust is crucial for fiscal performance using data for the full sample of Swiss cantons over the 1981-2001 period. In cantons with high levels of trust, the level of indebtedness is significantly lower. Trust supports fiscal discipline. In order to get a useful approximation for mutual trust among citizens and between citizens and their representatives, we use information from direct voter participation on political issues (initiatives and public referenda) held in Swiss state (cantonal) governments. Electoral support of government proposals reveals an important aspect of trust in a real world setting. Hence, our trust variable measures the behavior at the ballots thereby reducing possible subjective biases derived from surveys and questionnaires.
Keywords: 330; Trust; Social capital; Fiscal performance; Indebtedness